The Combination of Acupressure and Affirmation Relaxation as an Alternative Method to Increase Breast Milk Production and Breastfeeding Self-efficacy - Dita Rahmaika Arumsari; I Wayan Agung Indrawan; Endang Sri Wahyuni (Research Journal of Life Science, 2018)
Breastfeeding has been normative prevailing standard for feeding and fulfilling nutrition for baby due to its important benefit for mothers and her infant. The most common problem in breastfeeding is lack supply of breast milk after giving birth. The aim of this research was to prove that combination of acupressure and affirmation relaxation method was able to increase breast milk and improve breastfeeding self-efficacy of primiparous mothers in the postpartum period. The study design was true experimental with pre-test and post-test design. There were 24 primiparous mothers who were divided into two groups. Weighing test was used to measure breast milk production and breastfeeding self-efficacy was measured using Indonesian version of Breastfeeding Self-Efficacy Scale. Data were analyzed using Unpaired t-test and Mann Whitney test (α = 0.05). Based on the finding, we could conclude that combination of acupressure and affirmation relaxations could improve breast milk production (p = 0.033) and breastfeeding self-efficacy (p = 0.045) for primiparous mother in the postpartum period encountered in several Independent Midwifery Practice in Malang. This method might be used as a non-pharmacological treatment for postpartum mothers. Health practitioners should disseminate this technique so that postpartum mothers can do that by themselves.